(untitled) (Progressive Agriculture, 2018)
This study was conducted to determine the effect of phytogenic feed additive and prebiotic on vegetable protein base diet in broiler performance. A total of 90 chicks (Cobb-500) were weighted and randomly assigned to the three treatment groups (To, T1 and T2) and supplemented with either phytogenic feed additives or prebiotic and reared for 28 days. Data on live body weight, body weight gain, feed intake and feed conversion (FC) were taken at weekly interval. Results revealed that significant (P<0.05) increase in live body weight of broilers was evident in both phytogenic feed additive and prebiotic supplemented groups comparing to the control group at 4th weeks of age. No significant (P>0.05) differences were found in live weight gain among the treatment groups on weekly intervals along the whole experimental period. However, significant differences (P<0.05) were evident on cumulative weight gain at 3rd and 4th weeks of age. In case of feed intake at the age of 3rd and 4th weeks, significant (P<0.05) differences were obtained with decreased feed intake in both phytogenic feed additive and prebiotic supplemented groups comparing to the control group. In case of feed conversion (FC), there were significant (P<0.05) differences among the groups on 1st week and 4th week of age. Best FC was accounted for prebiotic supplemented group along the whole experimental period. The survivability rates were 96.67%, 100% and 100% in control group, phytogenic feed additive and prebiotic supplemented group respectively. Results finally showed that vegetable protein when supplemented with phytogenic prebiotic feed additives and prebiotic c an additive beneficial effect on performance of when compared to non-supplemented control diet. So, ration using vegetable protein mixed with phytogenic feed additives or prebiotic can be recommended for broiler. Progressive Agriculture 28 (4): 323-330, 2017